Comparative study of the positive value of unlawful testimony in civil proceedings - HASANZADEH, M.; ESMAILY, H. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT In the Islamic judicial system, testimony is one of the most important arguments to prove a claim. The validity of testimony depends on the credibility and the number of witnesses. If the testimony lacks the requisite terms and conditions, its validity is shaken. In this paper, we examine the "positive value of unqualified testimony" and refer to its jurisprudential background after presenting the contradictions and ambiguities of domestic law regarding the positive value of such testimony. From the nature of the jurisprudence’s testimony, it can be concluded that this type of testimony lacks any positive value. RESUMEN En el sistema judicial islámico, el testimonio es uno de los argumentos más importantes para probar un reclamo. La validez del testimonio depende de la credibilidad y el número de testigos. Si el testimonio carece de los términos y condiciones requeridos, su validez se ve sacudida. En este documento, examinamos el "valor positivo de un testimonio no calificado" y nos referimos a sus antecedentes jurisprudenciales después de presentar las contradicciones y ambigüedades de la ley interna con respecto al valor positivo de dicho testimonio. Por la naturaleza del testimonio de la jurisprudencia, se puede concluir que este tipo de testimonio carece de valor positivo.